The rise and fall of leader males in a multi‐level society: Takeovers and tenures of male hamadryas baboons. Issue 1 (12th September 2014) - Pines, Mathew; Chowdhury, Shahrina; Saunders, Julian; Swedell, Larissa
<x xml:space="preserve">Abstract</x> As one means to maximize access to females, males of some species are intolerant of other males in social units, resulting in female defense polygyny, a mating system in which one male monopolizes mating access to as many females as he can for as long as possible. In such a system, the length of a male's tenure and the number of females he is able to acquire are important predictors of his reproductive success. Hamadryas baboons differ from many other taxa with female defense polygyny in that they acquire and lose females individually, thus patterns of acquisition and loss of females over time are additional factors contributing to a male's fitness. Here, we describe longitudinal patterns of female acquisition and loss over a 9‐year period in a group of 250 wild hamadryas baboons. Complete tenures of leader males ranged from 310 to 2, 160 days (N = 13) and results from a survival analysis yielded a median tenure length of 2, 160 days, or 6 years (N = 49). The total number of females acquired, which increased with tenure length, ranged from 1 to 14 and averaged 3.5, and leader males acquired females both opportunistically and via challenging other males. The interval between acquisition of successive females ranged from 0 to 1, 196 days with a median of 203, and males acquired all of their females less than halfway into their tenure. Females from outside of a leader male's social sphere (clan and band) were acquired relatively later in their tenure compared to females from within a male's social sphere. Leaders typically lost females gradually during the latter part of their tenure or all (or most) at once, suggesting an inverted U‐shaped longitudinal arc of male competitive ability. Am. J. Primatol. 77:44–55, 2015. © 2014 Wiley Periodicals, Inc.